KEBERADAAN PERUSAHAAN PERKERETAAPIAN NEDERLANDSCH-INDISCHE SPOORWEG MAATSCHAPPIJ DI SEMARANG TAHUN 1863-1873 - Ningtyas, Endah Mustika (Historia, 2024)
This study examines the Nederlandsch-Indische Spoorweg Maatschappij (NISM) Company in 1863-1873 which was founded in Semarang. Transportation in the Dutch East Indies before 1863, especially the Semarang Residency area, still used simple transportation to deliver goods and people. The main issues studied in this article are the development of the NISM Company from its construction to the completion of the railway line, and the impact of the railway operation on the government and society. The transportation company first used an engine-powered train by making the Semarang Residency the starting point for the railway line as well as the main office of the NISM Company. The research method used as a form of historical study is the historical method. The results of the study explained that the establishment of the NISM Company in the Residency of Semarang was due to the need for a mode of transportation to transport Cultivation products from the interior to the port. Keywords: Semarang Residency; NISM Company; rail transportation